Bioinspired Superhydrophobic Surfaces via Laser-Structuring - Liu, Monan; Li, Mu-Tian; Xu, Shuai; Yang, Han; Sun, Hong-Bo (Frontiers in Chemistry, 2020)
Bioinspired superhydrophobic surfaces are a key artificial functional surface that mainly extracts morphological designs from natural organisms. How to develop large-area surfaces with water repellence is important for both laboratory research and industry. Nowadays, more severe requirements such as chemical-free treatment and high surface roughness are challenging current surface modification methods. Laser micro-nanofabrications are well-known for their non-contact processing and outstanding patterning ability. Herein, we briefly reviewed surface structuring toward superhydrophobic surfaces via multiple laser patterning methods